Analisis Reaksi Pasar Modal Sebelum dan Saat Peristiwa Pandemi Covid-19 (Studi Pada Perusahaan Sub Sektor Restoran, Hotel, Tourism Yang Tedaftar di Bursa Efek Indonesia Tahun 2020) - Alan Yulianza; Adria Wuri Lastari; Efandri Agustian (LPPM Universitas Adiwangsa Jambi, 2020)
This study was conducted to determine the difference before and during the Covid-19 Pandemic on the capital market reaction by using the Restaurant, Hotel, and Tourism subsector samples listed on the Indonesia Stock Exchange in the 2020 period. The population and sample in this study were the entire population, namely 31 sector companies. restaurant hotel and tourism This research is a quantitative research, the type of data using secondary data The research method that researchers use is summary. The results in this study indicate that the Covid-19 pandemic event had a fairly bad impact on the capital market. Based on the summary test results that have been carried out, it can be concluded that before and during the Covid-19 pandemic the Abnormal Return variable reacted negatively to the capital market reaction, it can be said that there was a difference between before and during the Covid-19 pandemic. For the Abnormal Return variable that has a negative reaction to the reaction of the capital market, it can be said that there is a difference between before and during the Covid-19 pandemic.